2011
DOI: 10.3233/nre-2011-0684
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging findings in neurologically asymptomatic patients with end stage renal disease

Abstract: Various neurological problems of the brain are known to occur in patients with end stage renal disease (ESRD). However, little is known about diffusion tensor imaging (DTI) findings in patients with ESRD. Using DTI, we attempted to investigate DTI findings in patients with ESRD who showed no specific lesions on conventional brain MRI. We recruited 10 consecutive patients with ESRD for whom at least 3 years had passed since the start of peritoneal dialysis and who showed no neurological abnormality on neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…These findings are supported by previously published neuroimaging results focused on other imaging techniques, such as MR spectroscopy (12,36), diffusion-tensor imaging (10,37), arterial spin-labeling MR imaging and voxel-based morphometry (9). Many previous investigators have demonstrated that multiple brain regions, especially the frontal and occipital or parietal lobes, had metabolic and structural abnormalities (ie, altered metabolites, diffusion-tensor tractography, cerebral blood flow, and cerebral atrophy) with cognitive decline in clinically asymptomatic stages in patients with ESRD.…”
Section: Discussionsupporting
confidence: 85%
“…These findings are supported by previously published neuroimaging results focused on other imaging techniques, such as MR spectroscopy (12,36), diffusion-tensor imaging (10,37), arterial spin-labeling MR imaging and voxel-based morphometry (9). Many previous investigators have demonstrated that multiple brain regions, especially the frontal and occipital or parietal lobes, had metabolic and structural abnormalities (ie, altered metabolites, diffusion-tensor tractography, cerebral blood flow, and cerebral atrophy) with cognitive decline in clinically asymptomatic stages in patients with ESRD.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have reported a correlation between MD and FA values and neuropsychiatric testing for patients with CKD, on hemodialysis, and after transplant [5052]. The use of advanced MRI measures such as DTI may provide a method to diagnose early risk of cognitive decline before symptom presentation [53]. Moreover, several newer MRI techniques are emerging such as multicomponent relaxometry techniques that may provide a tool to understand the etiology and the impact of risk factor contribution to cognitive decline in patients with renal disease [47, 5055].…”
Section: Brain Structure In Renal Diseasementioning
confidence: 99%
“…The ESRD patients without clinical signs of overt encephalopathy showed metabolic disturbances in distinct brain regions as well as cognitive impairments [7]. Kim et al used diffusion tensor imaging and found that neurologically asymptomatic patients with ESRD had abnormalities on diffusion tensor function, tractography that were associated with cognitions, including executive function attention, memory, or visuospacial function [15]. Prohovnik et al’ study showed that ESRD patients undergoing hemodialysis have generalized cerebral atrophy and focal degeneration of the head of the caudate nucleus [16].…”
Section: Introductionmentioning
confidence: 99%